The Xoraxane Roma of Chile: Ethnographic notes by a linguist - Irizarri, Pablo (Romano džaniben, 2021)
The Chilean Roma community predominantly belongs to a group who call themselves Xoraxaj or Xoraxané Rromá. They find their origins in early twentieth century Serbia and Bosnia and speak a Southern Vlax dialect. The present study introduces aspects of their lifestyle, history, identity, inter-ethnic relations and perceptions, religious and marital practices, and language. It is based on the author's recent fieldwork among Xoraxaj who lead an itinerant, tent-dwelling existence.
Keywords: Chile; Xoraxane; Roma; Serbia; Bosnia; Itinerance; Southern Vlax